The Determinants of the Incidence and the Effects of Overeducation in the Malaysian Labour Market - Zakariya, Zainizam (Asian Journal of Assessment in Teaching and Learning, 2013)
This paper attempts to study the quality of jobs match held by workers in the manufacturing sector of Malaysia. Relevant issues are thus covered: the incidence, determinants, and wage impacts of overeducation. Using the second Malaysia Productivity Investment Climate Survey (PICS-2), nearly 20% and 30% of workers are employed in jobs for which they are overeducated and undereducated, respectively. Further examination suggests that overeducation is not only due to lack of human capital accumulation (work experience and training) and soft skills, i.e. English proficiency, leadership, and creativity, but also related to firm characteristics in terms of firm size, the share of university workers at the workplace and hiring practice. Evidently, using augmented Mincer earnings equation signifies that being overeducated leads to a greater wage penalty. The return of surplus education (overeducation), in particular, is lower than the return of required education (6% against 10%) regardless of gender. This means that overeducated workers earn significantly lower than their co-workers who are in similar jobs but who have lower levels of education and well matched. The situation of overeducation among highly educated workers in the Malaysian labour market may impede the country’s intention to move towards the state of being a highincome country, as outlined in the “New Economic Model” blueprint.